Comparison of the Dentin Bond Strength of two Self-Etch Adhesives after Prolonged Air-Drying and Additional Light-Curing - Pouran Samimi; Masoud Ghodrati; Farinaz Shirban; Maryam Khoroushi (Tehran University of Medical Sciences, 2017)
Objectives: It has been reported that the water, solvents, or the primer incorporated into adhesive resins decrease the polymerization, compromise the mechanical properties, reduce the bond strength, and lead to a poor bonding performance of self-etch adhesives. This article evaluated the effect of air-drying and light-curing duration of self-etch adhesives on the micro-shear bond strength between composite resin and dentin. Materials and Methods: A total of 120 extracted sound human third molars were randomly divided into twelve groups (n=10). The occlusal dentin in each tooth was exposed. Clearfil SE Bond (CSEB) and Clearfil S3 Bond (CS3B) were used according to the manufacturer's instructions, followed by air-drying for 3 and 10 seconds in different groups. The adhesives were light-cured for 10, 20 and 40 seconds in different subgroups. Next, the composite resin (Clearfil AP-X) was placed on the dentin surface and was polymerized for 40 seconds. The micro-shear bond strength values were determined using a universal testing machine, and the results were statistically analyzed by three-way ANOVA and Tukey's post-hoc test (α=0.05). Results: CSEB exhibited a significantly higher dentin bond strength than CS3B. Increasing the curing time of CSEB resulted in an increase in the bond strength, whereas an increase in the air-drying time did not affect the bond strength of the two adhesives. Conclusions: Within the limitations of this study, an increase in the curing time improved the bond strength of CSEB, whereas the air-drying time did not affect the bond strength of the evaluated adhesives.